Endomembranes: Unsung Heroes of Mechanobiology? - Phuyal, Santosh; Baschieri, Francesco (Frontiers in Bioengineering and Biotechnology, 2020)
Mechanical stimuli have profound effects on the cellular architecture and functions. Over the past two decades, considerable progress has been made in unravelling the molecular machineries that confer cells the ability to sense and transduce mechanical input into biochemical signals. This has resulted in the identification of several force-sensing proteins or mechanically activated ion channels distributed throughout most cell types, whereby the plasma membrane, cytoskeleton and the nucleus have garnered much attention. Although organelles from the endomembrane system make up significant portion of cell volume and play pivotal roles in the spatiotemporal distribution of signaling molecules, they have received surprisingly little attention in mechanobiology. In this mini-review, we summarize results that document participation of the endomembrane system in sensing and responding to mechanical cues.